Research And Observations On Solar Storm: Solar Warning On 11 March 2015 - Setiahadi, Bambang (Universitas Muhammadiyah Surakarta, 2016)
On early morning on 11 March 2015 a solar exceptionally energy release was calculated by MHDoobservational parameters and showed there would be energy liberated by the Sun. Later we observed on 17 March 2015, we did notice geomagnetic large deviation. As preliminary conclusion we supposed that on 11 March 2015 the Sun did release huge energy into interplanetary space.